ANALISIS MANAJEMEN RANTAI PASOK PEMASOK LOKAL DI PT. PRASMANINDO BOGA UTAMA SITE BATU HIJAU, PT. AMMAN MINERAL NUSA TENGGARA, SUMBAWA BARAT, NUSA TENGGARA BARAT - Haryandi (JURNAL INDUSTRI DAN TEKNOLOGI SAMAWA, 2020)
A competitive business focuses on how to increase value to consumers byprovide products and services that are more valuable than competitors. Excellencebusiness competitiveness must be supported by strong Supply Chain Management (MRP). MRP representsthe process of creating value added goods and services that focuses on the efficiency and effectiveness ofinventory, cash flow, and information flow. PT. Prasmanindo Boga Utama (PTPBU) as the only catering service company in PT. Amman Mineral Nusa Tenggara (PTAMNT) Batu Hijau site,West Sumbawa, West Nusa Tenggara which is engaged in mining has involvedlocal suppliers to assist with the distribution of goods and services. The purpose of this research is to examinesupply chain management and distribution patterns of local suppliers of raw materials in local suppliers of raw materialsPTPBU Site Batu Hijau, PTAMNT. The research was conducted using qualitative methods, namely observation,in-depth interviews (in-depth interviews), and distribution of questionnaires to related partiesin research which contains a list of questions that are relevant to the purpose of the study. OnIn this research, it can be identified that the supply chain model of raw material suppliers in PTPBU is influenced bytypes of raw materials, members of the supply chain involved in it, and the system builtamong various parties. However, what drives the difference in supply chain liesat different suppliers. The raw materials consist of rice, catfish, watermelon, vegetables, tofutempeh, and packaged drinks. The distribution pattern of the supply chain for raw material suppliers at PTPBUstarting from independent farmers / breeders / producers then to suppliers / suppliers, after coming from the suppliercontinued to PTPBU and finally to PTAMNT.